The Role of Community Characters in Sending Cases of Sexual Violence against Children - Ernita Dewi; Said Amirulkamar (Budapest International Research and Critics University, 2020)
The changing times that are getting faster with the presence of communication technology have shifted many positive trasidies in society, turning into a new tradition that is more individualistic. One of them is the change in social institutions, community leaders, in Acehnese society, which can be said to be one of the local wisdoms. Social institutions consisting of village officials have the duty to protect, guard, supervise and resolve all problems that occur in the community. They are like a gampong fence that continues to protect society from all forms of crime and a-moral action, one of which is sexual violence against children and women. The rise in cases of sexual violence must be addressed, one of which is by optimizing the role of community leaders.